The fault in our stars - Green, John 1977- (National Book Store, 2014)
Sixteen-year-old Hazel, a stage IV thyroid cancer patient, has accepted her terminal diagnosis until a chance meeting with a boy at cancer support group forces her to reexamine her perspective on love, loss, and life. Despite the tumor-shrinking medical miracle that has bought her a few years, Hazel has never been anything but terminal, her final chapter inscribed upon diagnosis. But when a gorgeous plot twist named Augustus Waters suddenly appears at Cancer Kid Support Group, Hazel's story is about to be completely rewritten.